Diagnosis of human envenoming by terrestrial venomous animals: Routine, advances, and perspectives - Joeliton S. Cavalcante; Sabrina Santana Toledo Arruda; Pedro Marques Riciopo; Manuela Pucca; Rui Seabra Ferreira Junior (Toxicon: X)
Despite the development of new and advanced diagnostic approaches, monitoring the clinical evolution of accidents caused by venomous animals is still a challenge for science. In this review, we present the state of the art of laboratory tests that are routinely used for the diagnosis and monitoring of envenomings by venomous animals, as well as the use of new tools for more accurate and specific diagnoses. While a comprehensive range of tools is outlined, comprising hematological, biochemical, immunoassays, and diagnostic imaging tools, it is important to acknowledge their limitations in predicting the onset of clinical complications, since they provide an overview of organic damage after its development. Thus, the need for discovery, validation, and use of biomarkers that have greater predictive power, sensitivity and specificity is evident. This will help in the diagnosis, monitoring, and treatment of patients envenomated by venomous animals, consequently reducing the global burden of morbidity and mortality.